The first year experience of occupational therapy students at an Australian regional University: Promoting student retention and developing a regional and remote workforce - Boehm, J.; Cordier, Reinie; Thomas, Y.; Tanner, B.; Salata, K. (2015)
Objective: Student retention at regional universities is important in addressing regional and remote workforce shortages. Students attending regional universities are more likely to work in regional areas. First year experience at university plays a key role in student retention. This study aimed to explore factors influencing the first year experience of occupational therapy students at a regional Australian university. Design: Surveys were administered to 58 second year occupational therapy students in the first week of second year. Data were analysed using descriptive statistics, inferential statistics (Pearson χ2; Spearman rho) and summarising descriptive responses. Setting: An Australian regional university. Participants: Second year undergraduate occupational therapy students. Main outcome measures: Factors influencing students' decisions to study and continue studying occupational therapy; factors enhancing first year experience of university. Results: Fifty-four students completed the survey (93.1%). A quarter (25.9%) of students considered leaving the course during the first year. The primary influence for continuing was the teaching and learning experience. Most valued supports were orientation week (36.7%) and the first year coordinator (36.7%). Conclusion: The importance of the first year experience in retaining occupational therapy students is highlighted. Engagement with other students and staff and academic support are important factors in facilitating student retention. It is important to understand the unique factors influencing students' decisions, particularly those from regional and remote areas, to enter and continue in tertiary education to assist in implementing supports and strategies to improve student retention.